Post‐transplant cyclophosphamide limits reactive donor T cells and delays the development of graft‐versus‐host disease in a humanized mouse model. Issue 2 (13th June 2021) - Adhikary, Sam R.; Cuthbertson, Peter; Nicholson, Leigh; Bird, Katrina M.; Sligar, Chloe; Hu, Min; O'Connell, Philip J.; Sluyter, Ronald; Alexander, Stephen I.; Watson, Debbie
Abstract: Graft‐versus‐host disease (GVHD) is a major complication of allogeneic haematopoietic stem cell transplantation (allo‐HSCT) that develops when donor T cells in the graft become reactive against the host. Post‐transplant cyclophosphamide (PTCy) is increasingly used in mismatched allo‐HSCT, but how PTCy impacts donor T cells and reduces GVHD is unclear. This study aimed to determine the effect of PTCy on reactive human donor T cells and GVHD development in a preclinical humanized mouse model. Immunodeficient NOD‐ scid ‐IL2Rγ null mice were injected intraperitoneally (i.p.) with 20 × 10 6 human peripheral blood mononuclear cells stained with carboxyfluorescein succinimidyl ester (CFSE) (day 0). Mice were subsequently injected (i.p.) with PTCy (33 mg kg −1 ) (PTCy‐mice) or saline (saline‐mice) (days 3 and 4). Mice were assessed for T‐cell depletion on day 6 and monitored for GVHD for up to 10 weeks. Flow cytometric analysis of livers at day 6 revealed lower proportions of reactive (CFSE low ) human (h) CD3 + T cells in PTCy‐mice compared with saline‐mice. Over 10 weeks, PTCy‐mice showed reduced weight loss and clinical GVHD, with prolonged survival and reduced histological liver GVHD compared with saline‐mice. PTCy‐mice also demonstrated increased splenic hCD4 + :hCD8 + T‐cell ratios and reduced splenic Tregs (hCD4 +  hCD25 +  hCD127 lo ) compared with saline‐mice. This study demonstrates that PTCy reduces GVHD in a preclinical humanized mouse model. This corresponded to depletion of reactive human donor T cells, but fewer human Tregs. Abstract : Graft‐versus‐host disease is a life‐threatening complication of bone marrow transplantation. Post‐transplant cyclophosphamide (PTCy) reduces clinical GVHD, but the mechanism is unclear. Using a humanized mouse model of GVHD, we demonstrate that PTCy not only reduces GVHD alongside reactive donor T cells in the liver, but also reduces human regulatory T cells, which are protective against disease.